Genome-Wide Identification, Characterization, and Expression Analysis of Orphan Genes Within Coriander - Meidi Zhang; Mo Zhu; Hong Lang; Weiming Wang; Xiaonan Li; Mingliang Jiang (Plants)
Orphan genes (OGs) are genes that have no significant sequence similarity with known genes from other species or lineages. Identifying and characterizing OGs have become more feasible with the increasing availability of plant transcriptomes and genome sequences. OGs play important roles in response to both biotic and abiotic stresses, contributing to biological functions and lineage-specific traits. This study aimed to identify and characterize OGs in Coriandrum sativum (coriander) using the BLAST method. A total of 941 C. sativum OGs (CsOGs), 1298 Apiaceae-specific genes (ASGs), and 38,508 evolutionarily conserved genes (ECGs) were identified through comparative genomics. Genic feature analyses revealed that CsOGs and ASGs, although part of different gene sets, had shorter gene lengths, a lower proportion of multi-exon genes, and higher GC content than ECGs. OGs were distributed across all 11 chromosomes, with the highest proportion of CsOGs and ASGs found on chromosome A11. RNA-Seq analysis revealed 71 CsOGs uniquely expressed in four different tissues, 61 CsOGs specifically expressed across three growth stages, and five CsOGs with specific expression patterns in different tissues and growth stages. Notably, as determined via qRT-PCR analysis, these five CsOGs presented general or specific expression patterns under normal conditions, but their expression significantly increased after exposure to cold stress, suggesting that they may play a critical role in cold stress response. This study comprehensively identified, characterized, and analyzed the expression of OGs within coriander, which provides a foundation for further research on the functions of coriander OGs in influencing species-specific trait formation and stress response.